Two new species of the genus Sweltsa (Plecoptera: Chloroperlidae) from China - Zhang, Yao; Wang, Bingli; Li, Wenliang; Li, Weihai (Zootaxa, 2023)
Two species of the genus Sweltsa Ricker, 1943 from China are described and figured as new to science. The morphological distinction between the new species and their similar relatives is discussed.